A periodization approach to building confidence in athletes. Issue 1 (2nd January 2019) - Vealey, Robin S.
Abstract: The purpose of this article is to describe a periodized, or temporally phased, approach to building confidence in athletes. A periodization approach to building confidence involves helping athletes move through the sequential phases of developmental, preparatory, and performance confidence that lead into Execution Mode just prior to and during the competitive event. An evaluation phase after the event is then integrated into the process of developmental confidence to continue the periodization cycle. Examples of the focus needed and specific activities that could be used in each confidence-building phase are provided.